(untitled) (Journal of the College of Basic Education, 2026)
This study aims to examine the manifestations of multilingualism and diglossia in the Arab digital space and to analyze the impact of the interaction between Modern Standard Arabic and colloquial dialects in texts circulated on social media platforms. The study is based on the assumption that the digital environment has contributed to reshaping the linguistic practices of Arab users due to its rapid communication, spontaneity of expression, and the absence of strict linguistic regulation. This situation has led to the emergence of new linguistic patterns, including a “middle language” and hybrid writing forms such as Arabizi or Franco, which rely on the use of Latin letters and numbers to represent Arabic sounds. The research adopts the descriptive-analytical method by examining samples of digital texts shared on social media and linking them to theoretical frameworks in contemporary linguistic and sociolinguistic studies. The findings reveal several linguistic phenomena, most notably the relaxation of some grammatical rules, syntactic reduction, and the increasing mixing of Standard Arabic and colloquial dialects in digital discourse. The study concludes that this linguistic interaction reflects the transformations imposed by the digital communicative environment and is influenced by technological, social, and cultural factors. It also indicates that the continued spread of such practices without sufficient linguistic awareness may affect the structural integrity of the Arabic language and its connection to cultural identity.